Math, asked by Anonymous, 7 months ago

Question:-
1) By taking x=3/5 and y=4/9, find out whether
(x + y {)}^{ - 1} =  {x}^{ - 1}  +  {y}^{ - 1}
is true or false.

2).ADD THESE RATIONAL NUMBERS:-

1)(-2)/5 and 3/4

2)5/8 and (-11)/12

3)7/(-18)+5/(-12)+(-9)/(-16)

Please solve fast in detail please!!!

Answers

Answered by JuniorBrainly100
22

GIVEN:-

By taking x=3/5 and y=4/9, find out whether

(x + y {)}^{ - 1} = {x}^{ - 1} + {y}^{ - 1}

is true or false.

TO FIND:-

(x + y {)}^{ - 1} = {x}^{ - 1} + {y}^{ - 1} is true or false.

SOLUTION:-

x + y =  \frac{3}{5} +  \frac{4}{9} =  \frac{3 \times 9 + 4 \times 5}{45}   \\  \\  \\  =  >  \frac{27 + 20}{45} \\  \\  \\  =  >  \frac{47}{45}  \\  \\  \\ (x + y {)}^{ - 1} =  \binom{4 {7}^{ - 1} }{45} =  \frac{45}{47}. \\  \\  \\  =  >  {x}^{ - 1} =  \binom{ {3}^{ - 1} }{ {5}^{} } \\  \\  \\  =  >  {y}^{ - 1} =  \binom{ {4}^{ - 1} }{9} \\  \\  \\  =  >  \frac{9}{4} \\  \\  \\ so.. {x}^{ - 1}  +  {y}^{ - 1} =  \frac{5}{3} +  \frac{9}{4} \\  \\  \\  =  >  \frac{5 \times 4 + 9 \times 3}{12}  \\  \\  \\  =  >  \frac{20 + 27}{12} \\  \\  \\  =  >  \frac{47}{12}. \\  \\  \\ this \: shows \: that \: (x + y {)}^{ - 1}not \: equal \:  to \:  {x}^{ - 1}  +  {y}^{ - 1}

\small\bold\red{Hence, \: The \: given \: statement \: is \: false!}

GIVEN:-

Add these rational numbers.

TO FIND:-

Sum of (-2)/5 and 3/4.

SOLUTION:-

The L.C.M. of 5 and 4 is 20.We express the given numbers with common denominator 20.

(-2)/5=(-2)×4/5×4=(-8)/20

3/4=3×5/4×5=15/20.

:. (-2)/5+3/4=(-8)/20+15/20

=>7/20

NOTE THAT: we have obtained the above working (-2)/5+3/4 as (-8)+15/20.

The last step is actually (-2)×4+5×3/5×4.

In general, if a/b and c/d are two rational numbers then

===================================

《a/c+c/d=a×d+b×c/b×d=ad+bc/nd.》

================================

TO FIND:-

The sum of 5/8 and (-11)/12

SOLUTION:-

hey mate!You could sorten you work as under!

5/8+(-11)/12=5×3+(-11)×2/24=15-22/24

=>(-7)/24.

see below↘⬇↙

1)Divide L.C.M. 24 by denominator 8.The quotient is 3.Multiply 5 by 3.

2)Divide L.C.M.24 by denominator 12.The quotient is 2.Multiply (-11) by 2.

Clarification:-

 \\  \\  \\  \frac{a}{b} +  \frac{c}{d} =  \frac{a \times \frac{l.c.m}{b} + c \times \frac{l.c.m}{d}  }{l.c.m \: of \: b \: and \: d} \\  \\  \\

TO FIND:-

The sum of 7/(-18)+5/(-12)+(-9)/(-16)

SOLUTION:-

First write the given rational numbers with positive d enominators.

=>7/(-18)= 7×(-1)/(-18)×(-1)=(-7)/18

=>5/(-12)=5×(-1)/(-12)×(-1)=(-5)/12

=>(-9)/(-16)=(-9)×(-1)/(-16)×(-1)=>9/6

Now,L.C.M.of 18,12&16 is 114.

So,

(-7)/18+(-5)/12+9/16=(-7)×8+(-5×12)+(9×9)/144

=>(-56)-60+81

(-35)/144

Hope it helped!

Answered by KittyFarily
1

\huge \bf Given  :-

\bf \red{1) By \:  taking \:  x= \frac {3}{5}  \: and \:  y =  \frac{4}{9}, find \:  out \:  whether  \: (x + y {)}^{ - 1} = {x}^{ - 1} + {y}^{ - 1}</p><p>is  \: true \:  or  \: false.}

 \bf \huge Solution :-

\bf \green {Hence, \: The \: given \: statement \: is \: false.}

\huge \bf Given  :-

  • \bf \red{(1) \:  \frac{( - 2)}{5} \: and \:  \frac{3}{4} }
  • \bf \red{(2) \:  \frac{5}{8} \: and \:  \frac{( - 11)}{12} }
  • \bf \red{(3) \:  \frac{7}{(-18)}+ \frac{5}{(-12)}+ \frac {(-9)}{(-16)}}

 \bf \huge Solution :-

  • \bf \red{(1) \:  \frac{( - 2)}{5} \: and \:  \frac{3}{4} =}\bf \green{0.35}
  • \bf \red{(2) \:  \frac{5}{8} \: and \:  \frac{( - 11)}{12} =}\bf \green{-0.29166666666}
  • \bf \red{(3) \:  \frac{7}{(-18)}+ \frac{5}{(-12)}+ \frac {(-9)}{(-16)}=}\bf \green{-0.24305555555}
Similar questions